Toward an Evaluation of an Integrated Clinical Imaging System: Identifying Clinical Benefits - Kaplan, B.; Lundsgaarde, H. P. (Methods of Information in Medicine, 1996)
Integrated clinical imaging systems can provide the foundation for future computer-based patient record systems as recommended by the Institute of Medicine. However, documenting the benefits of such systems is difficult. This paper reports an evaluation of a clinical imaging system that is integrated with an on-line electronic patient record. The evaluation used interviews and observations to identify what physicians thought were the benefits of this system. Reported benefits may be classified into patient care benefits, educational benefits, and productivity and cost-reduction benefits. Physicians said that the imaging system provided patient care benefits by: improving clinical communication and decision making, making care more patient-based, reducing the number of procedures and patient risks, and improving record keeping. Educational benefits they reported included: improving communication, providing broad “real” experience, and improving supervision. These benefits may be reflected in increased productivity and cost reduction by increasing time savings, reducing clerical work, improving morale, and reducing the costs of care. The approach described in this study was valuable in identifying potential benefits of a clinical information system. The findings point the way to realization of benefits for other systems, and, ultimately, for computer-based patient records.
Keywords: Evaluation; Imaging; Computer-based Patient Record; Clinical Benefits; PACS; Organizational Aspects